Buckling phenomena in AM lattice strut elements: A design tool applied to Ti-6Al-4V LB-PBF. (October 2021) - Alghamdi, Ahmad; Downing, David; Tino, Rance; Almalki, Abduladheem; Maconachie, Tobias; Lozanovski, Bill; Brandt, Milan; Qian, Ma; Leary, Martin
Graphical abstract: Highlights: A fundamental review of column buckling theory relevant to the performance of as-manufactured additively manufactured strut elements. Experimental data provides new insight into the effect of salient design features on the associated buckling response. Euler buckling analysis overpredicts the buckling response of the as-manufactured strut elements. Non-linear numerical models based on Micro CT data provided accurate prediction of critical buckling loads. Effective eccentricity ratio is shown to increase non-linearly with increasing slenderness ratio. Abstract: Additive Manufacturing (AM) technologies such as Laser-Based Powder Bed Fusion (LB-PBF) enables the manufacturing of high efficiency lattice structures. However, the LB-PBF processes inherently generate local geometric effects. The practical implications of these geometric effects on structural performance is of critical importance to effective AM design; however, these effects are poorly understood. In response to this uncertainty, this research compares predictive and experimental data for the structural response of LB-PBF lattice strut elements subject to compressive loading; this comparison is made for LB-PBF manufactured Ti-6Al-4V LB-PBF but is generally applicable to all AM systems and materials. This data provides insight into the influence of geometric design parameters, including: node and strut diameter, strut length, and manufacturing inclination angle. The effect of these geometric parameters on the associated critical buckling load, and the accuracy of predictive failure models is quantified. Furthermore, the eccentricity ratio, a classical measure of column efficiency widely used in civil engineering design, is applied for the first-time as a systematic metric to characterise the structural efficiency of as-manufactured AM strut element.